2009
DOI: 10.1016/j.bbrc.2009.01.136
|View full text |Cite
|
Sign up to set email alerts
|

Poly(C)-binding proteins as transcriptional regulators of gene expression

Abstract: Poly(C)-binding proteins (PCBPs) are generally known as RNA-binding proteins that interact in a sequence-specific fashion with single-stranded poly(C). They can be divided into two groups: hnRNP K and PCBP1-4. These proteins are involved mainly in various posttranscriptional regulations (e.g., mRNA stabilization or translational activation/silencing). In this review, we summarize and discuss how PCBPs act as transcriptional regulators by binding to specific elements in gene promoters that interact with the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 45 publications
(65 reference statements)
7
84
0
1
Order By: Relevance
“…However, we did not find evidence that hnRNP K affects the stability of FLIP mRNA (Figure 3c), although FLIP mRNA could be regulated by IRF8 through mRNA stabilization. 37 Instead, similar to the hnRNP K-mediated induction of c-myc, Src and eIF4E gene expression through binding of poly(C) elements in their gene promoters, 1 we herein show that the poly(C) element of the FLIP promoter is important for its recognition and activation by both hnRNP K and nucleolin.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, we did not find evidence that hnRNP K affects the stability of FLIP mRNA (Figure 3c), although FLIP mRNA could be regulated by IRF8 through mRNA stabilization. 37 Instead, similar to the hnRNP K-mediated induction of c-myc, Src and eIF4E gene expression through binding of poly(C) elements in their gene promoters, 1 we herein show that the poly(C) element of the FLIP promoter is important for its recognition and activation by both hnRNP K and nucleolin.…”
Section: Discussionsupporting
confidence: 66%
“…Analysis of the FLIP promoter sequence revealed four potential hnRNP K-binding poly(C) or C-C-C-C elements, R1 to R4 (Figure 3a). 1 To distinguish between transcriptional activation and post-transcriptional regulation, we examined the effect of hnRNP K knockdown on FLIP promoter activity and mRNA stability. We transfected a FLIP promoter reporter construct (À1179 to þ 281) into hnRNP K-knockdown NPC-TW02 cells and examined reporter activity 24 h later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied this Fully Automated and Standardized iCLIP (FAST-iCLIP) pipeline to a published iCLIP data set of the RBP hnRNP-C, recapitulating the published biology of this protein. We then applied FAST-iCLIP to the human and viral interactomes of Poly-C binding protein 2 (PCBP2), a KH domain (hnRNP-K homology) (Lunde et al 2007) containing RBP that has a preference for C/Urich motifs (Choi et al 2009) as well as pathological associations in cancer (Eiring et al 2010;Han et al 2013) and infectious disease (Gamarnik and Andino 2000;Herold and Andino 2001;Shetty et al 2013). The unbiased characterization of the PCBP2 protein revealed novel RNAprotein interactions and provided supporting evidence for previously known cellular and viral roles for PCBP2.…”
Section: Introductionmentioning
confidence: 78%
“…PCBP2 has a preference for C-rich motifs (Choi et al 2009) and notable association with infectious disease (Han et al 2013). PCBP2 was a favorable target, as features of its biology are well understood, but no CLIP-seq study has been reported to date (Waggoner and Liebhaber 2003;Han et al 2013).…”
Section: Resultsmentioning
confidence: 99%